Computational study of Staggered and Double Cross Flow Heat Exchanger - Krishnan, Annur Srinivasan; Gowtham, Palanivelu (Defence Science Journal, 2017)
The preliminary findings of a comparative study of heat transfer rate and pressure drop between conventional staggered flow and double cross flow heat exchanger is reported. Excepting for the tube arrangements, the shell and tube dimensions, materials and inlet conditions are retained the same for the two configurations. While in the conventional arrangement, adjacent rows of tubes are normal only to the fluid flow in the shell, in the double cross-flow arrangement, they are normal to both fluid flow direction in the shell as well as to each other. Shell dimensions are 100 cm × 20 cm × 20 cm and tube outside and inside diameters are 1 cm and 0.8 cm. The shell and tube materials are steel and copper. Water and air were considered as tube and shell side fluids respectively, with an overall arrangement of parallel flow. The tube flow Reynolds number was fixed at 2200 and the shell flow Reynolds number was varied from 20 to 120 in the laminar regime and 360 to 600 in the turbulent zone. The study reveals that the proposed configuration gives a maximum increase of about 27 per cent in the heat transfer rate per unit pressure drop over the conventional one.